(untitled) (BIRDEM Medical Journal, 2012)
Objective: The present study was undertaken to determine the association of maternal serum HbA1C level with maternal and fetal outcome. Materials and Methods: It was prospective observational study. The study was carried out in the department of Obstetrics and Gynaecology in BIRDEM Hospital during the period of September 2006 to August 2007. During this study period, 100 pregnant patient with diabetes who attended or admitted at BIRDEM Hospital were studied. Estimation of serum HbA1C level was done in all patient in each trimester. From each patient 5 c.c blood was taken & HbA1C level was measured with the help of enzymatic method. HbA1C level < 6 was considered as normal. .The maternal complications in antenatal period, in postpartum period, during labour & fetal outcome were studied in both cases of controlled & uncontrolled HbA1C level. Result: In this study serum HbA1C level was found raised in uncontrolled diabetic patients. The incidence of vulvovaginitis, preterm delivery and polyhydramnios were significantly high in 2nd and 3rd trimester in raised HbA1C level. The rate of normal vaginal delivery was higher in patient with normal HbA1C leve uncontrolled HbA1C level (17.59% Vs 10.84%, p = 0.01), which statistically significant. Post partum haemorrhage (PPH) was significantly higher in raised HbA1C level than normal (0.00% Vs 22.20%, p =0.01) in NVD and (0.00% Vs 16.22%, p = 0.01) in Caesarean section. Neonatal complications were higher in raised HbA1C level than normal. The incidence of Hypoglycemia (5.88% Vs 38.55%, p = 0.02); Hyperbilirubinemia (11.76% Vs 33.73%, p = 0.03) ; RDS (0.00% Vs 12.05%, p = 0.02); Macrosomia (0.00% Vs 18.07%,p = 0.01) and Birth asphyxia (5.88% Vs. 12.05%, p = 0.04). These differences are statistically significant. Conclusion: There is increasing evidence that the raised level of maternal serum HbA1C in antenatal period is associated with maternal & neonatal complications. By investigating HbA1C level in each trimester, blood sugar control can be done. This study was taken out to evaluate the usefulness of HbA1C for good glycaemic control in diabetic pregnancy. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12358 Birdem Med J 2012; 2(1) 23-28